Self-Reported Side Effects of Different COVID-19 Vaccines in Bangladesh- A Vaccine Recipient Survey - Chowdhury, Mohammad Tawfique Hossain; Somrat, K M Tawsif Ahamed; Rashid, Maliha; Nath, Sujan Kanti; Siddika, Aeysha; Kabir, Russell (Update Dental College Journal, 2023)
Background: COVID-19 (Corona Virus disease 2019) is a newly discovered disease that originated in China and quickly spread throughout the world, killing millions of people and infecting many more. People have a new hope due to newly discovered vaccines for this fatal disease. However, the vaccines showed a number of side effects on the people receiving them. Nonetheless, it has proven to be helpful in providing protection against the fatal infection. Purpose: To analyze the probable side effects of the vaccines experienced by vaccine recipient and their belief regarding vaccine. Method: An online survey was conducted through different social media platforms and Email from 11 July’2021 to 16 July’2021. Ethical permission and consent was taken prior to the survey and data collections. Occurance and the extent of vaccine side effects were analyzed using descriptive and logistic regression analysis. Result: Among 175 vaccine recipients, 92 (52.58%) received one dose and 83 (47.42%) received two doses, with 93 (53.1) receiving SinoPharm vaccine, 78 (44.6) receiving AstraZeneca vaccine, and 4 (2.3%) receiving Pfizer vaccine. More than half of the respondents experienced side effects among which headaches (50.3%) and drowsiness (45.71%) were common followed by fever (36%) and muscle ache (32%). Female (P=0.000) and vaccine concerned group (P=0.033) experienced more side effects. Headache (68.8%), fever (40.9%) and drowsiness (50.5%) were more common among Sinopharm recipients. Fever (50%) and muscle ache (50%) were more common among Pfizer recipients while muscle ache (43.5%) and drowsiness (42.3%) were common among AstraZaneca recipients group. Conclusion: Headache, fever, muscular discomfort, soreness at the injection site, drowsiness, nausea, and other adverse effects are common with the COVID vaccination. Females are more susceptible to side effects than males, and the probability of experiencing them increases with the second dose. AstraZeneca vaccine recipient experiencing more side effects than other types of vaccine recipients. Update Dent. Coll. j: 2023; 13(2):3-8